The Impact of Mining on Labor Absorption and the Economy of Working Families in Lasolo District, North Konawe Regency - Devi Safitri; La Ode Turi; Kartomo, Kartomo (Teras Kampus, 2024)
This research aims to measure the impact of PT. XYZ towards employment and the economy of working families in North Konawe Regency. The research method used is qualitative using primary and secondary data. Data was obtained from the Central Bureau of Statistics and Company Data, with data collection techniques including observation, interviews and documentation. The research results show that the existence of PT. XYZ in Lasolo District, North Konawe Regency absorbs 35 workers from the local area and 15 workers from outside the area. Even though the number of employees is only 50 people, this company's contribution to employment reaches 0.10% of the total workforce in North Konawe. However, the role of PT. XYZ supports the economy of working families quite significantly, with an average contribution reaching 91.39% of family income. This shows that even though the number of workers absorbed is relatively small, the economic impact is quite large for the families of the workers involved.